Dual-emissive mitochondrial sensor for simultaneous monitoring of ONOO− and viscosity changes in liver disease diagnosis - Qianqian Gao; Dae-Kyun Lee; Jindong Dai; Dongwei Zhu; Junshuai Ma; Kanagaraj Rajalakshmi; Dae-In Oh; Yun-Sik Nam; Ki Young Choi; Selvaraj Muthusamy; Jong-Won Song; Yuefan Zheng; et al. (Analytica Chimica Acta, 2026)

Camellia sinensis (L.) mitigates copper oxide nanoparticles-induced lung inflammation and mucus production through suppressing MAPK signaling and MUC5AC - Woong-Il Kim; Seol Jang; So-Won Pak; Sin-Hyang Park; Ba-Reun Jin; Jong-Choon Kim; Changjong Moon; Joong-Sun Kim; Young-Kwon Cho; Taesoo Kim; In-Sik Shin (Molecular & Cellular Toxicology, 2026)

AI-driven non-intrusive occupant monitoring for occupant-centric control: A multi-domain review of thermal, air, and visual environments - Ji Young Yun; Jin Woo Moon; Kang Woo Bae; Jun Kyu Kim; Hae Won Lee; Hye In Kim; Jae Ho Sung; Michael Kim (Building and Environment, 2026)

Development of Novel Host-Associated Low-Temperature Probiotics (HALP) Tailored to Aquaculture Applications - Su-Jeong Lee; Young-Sun Lee; Yu-Ri Kim; Mi-Hyeon Jeon; Da-In Noh; Seong-Mok Jeong; Kang-Woong Kim; Eun-Woo Lee; Won Je Jang (Probiotics and Antimicrobial Proteins, 2026)

Probiotic-Derived Strain-Specific Metabolites Ameliorate Metabolic Dysfunction–Associated Steatotic Liver Disease through Modulation of the Gut-Liver Axis - Sang Jun Yoon; Jieun Choi; Sung-Min Won; Jeong Seok Yu; Hee Young Kim; Hyun Chae Joung; In Gyu Park; Jung A Eom; Sang Hak Han; Do Yup Lee; Ki Tae Suk (Probiotics and Antimicrobial Proteins, 2026)

Long-term continuous operation of a 3-MWth chemical looping combustion system for steam generation and CO2 separation - Yooseob Won; Byung Wook Hwang; Yujin Choi; Jae-Young Kim; Hana Kim; Jeongmin Kim; Yuntae Hwang; Daewook Kim; Myounghoon Choun; Jeom-In Baek; Ho-Jung Ryu (Chemical Engineering Journal, 2026)

Characterization and comparative analysis of saponins in various spinach (Spinacia oleracea L.) cultivars according to growing seasons - Su-Yeon Lee; Doo-Young Kim; Hyun-Jae Jang; Seon Min Oh; Hyoung-Geun Kim; Jongmin Ahn; In-Seo Heo; Heung Joo Yuk; Eun Kyoung Seo; Sei-Ryang Oh; Hyung Won Ryu (Food Chemistry, 2025)

Effects of web-based behavioral intervention on fine particulate matter, pulmonary function, and airway inflammation in children: The COCOA randomized controlled trial - Dirga Kumar Lamichhane; Bo-Mee Kim; Jungyun Bae; Hea Young Oh; Dong In Suh; Youn Ho Shin; Kyung Won Kim; Kangmo Ahn; Hyo-Bin Kim; Song-I Yang; So-Yeon Lee; Soo-Jong Hong; et al. (Environmental Research, 2025)

Hybrid W-MgF2/graphene photothermal membrane for efficient solar-driven desalination - Ga Eun Lee; Jinsoo Cho; In-Young Jung; Da Seul Kim; Seok Joon Kwon; Won Jun Choi; Kyung Guen Song; Hak Ki Yu; Jeong Min Baik (Desalination, 2025)

Physiological Effects of Suspended Solids on Venerupis philippinarum and Argopecten irradians - Ha-Jeong Son; Ju-Won Kim; Min-Young Sohn; Chae-yeong Ji; Su Bhin Jeong; In Gu Kim; Jung-Ha Kang; Hee Jeong Kong; Chan-Il Park; Gyoungsik Kang (Fishes, 2025)
Suspended solids are small particles transported in the water column, which can damage marine ecosystems and impair the health of aquatic organisms. This study evaluated the physiological responses of clams (Venerupis philippinarum) and Atlantic Bay scallops (Argopecten irradians) to suspended solid exposure. Four concentrations (100–1000 mg/L) were tested, with a control group maintained at 0 mg/L. At each time point (1, 2, 4, 6, 8, and 12 days), hemolymph samples were collected from five individuals per group to measure GOT, GPT, ALP, and cortisol. Exposure to suspended solids significantly increased these biochemical indicators compared with the control. Quantitative survival analysis showed that Venerupis philippinarum survival declined to 83.3% (25/30) at 500 mg/L and 76.7% (23/30) at 1000 mg/L after 5 days, while the control maintained 100% survival. In Argopecten irradians, survival remained close to 100% in most treatments, with a slight reduction to 83.3% (25/30) at 1000 mg/L. No mortality occurred in the control group without suspended solids, whereas mortality was evident under combined temperature stress and suspended solid exposure. These findings demonstrate that suspended solids induce stress responses in both species, with early mortality in Venerupis philippinarum likely caused by particle adhesion to the gills, leading to reduced respiratory efficiency.

Long-acting injectable delivery system comprising ordered mixed drug aggregates with deaggregating and uniformly embeddable viscoelastic -polysaccharide solutions - Jun Soo Park; Dong Gun Lee; Jin Hyuk Myung; Min Young Jeong; In Gyu Yang; Gi Yeong Lee; Ji Won Yeo; Chae Won Park; Jin Hwan Kim; Ye Bin Shin; Myoung Jin Ho; Sung Giu Jin; et al. (Carbohydrate Polymers, 2025)

Reaction mechanism and kinetics on the methanolysis–esterification–lactonization of α-phellandrene-derived cyclic acid anhydride - Seong-Min Cho; Won-Sil Choi; Young-Min Cho; Soo Min Lee; Bonwook Koo; In-Gyu Choi (Journal of Environmental Chemical Engineering, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Bacillus velezensis CE 100 controls anthracnose disease in walnut trees (Juglans regia L.) by inhibiting Colletotrichum gloeosporioides and eliciting induced systemic resistance - Vantha Choub; Sang-Jae Won; Jae-Hyun Moon; Su-In Choi; Henry B. Ajuna; Young Sang Ahn (Biotechnology Letters, 2025)

Dexamethasone nanocrystals-embedded hydroxypropyl methylcellulose hydrogel increases cochlear delivery and attenuates hearing loss following intratympanic injection - Min Young Jeong; Subin Kim; Hye Rim Kim; Jiae Jeon; Seong Su Won; Keum-Jin Yang; Jun Soo Park; In Gyu Yang; Dong Geon Lee; Jin Hyuk Myung; Yoon-Gyoon Kim; Sung Giu Jin; et al. (Carbohydrate Polymers, 2024)

A new neo-lignan from culture broth of Phellinus linteus and its dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Ji-Yul Kim; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Ultrathin Two-Dimensional Ordered Porous Carbon Host with Atomically Dispersed Electrocatalytic Sites toward High Volumetric Energy Lithium-Sulfur Battery - Won-Gwang Lim; Minkyeong Ban; Kyu In Shim; Jinkyu Park; Seongbeen Kim; Seongseop Kim; Seoa Kim; Cheol-Young Park; Jeong Woo Han; Jinwoo Lee (Chemical Engineering Journal, 2024)

Lacticaseibacillus paracasei completely utilizes fructooligosacchrides in the human gut through β-fructosidase (FosE) - Dong-Hyun Jung; In-Young Kim; Ye-Jin Kim; Won-Hyong Chung; Mi-Young Lim; Young-Do Nam; Dong-Ho Seo; Cheon-Seok Park (World Journal of Microbiology and Biotechnology, 2024)

Polyhexamethylene guanidine phosphate induces pyroptosis via reactive oxygen species-regulated mitochondrial dysfunction in bronchial epithelial cells - Jun Young Park; Ji-Hee Kim; Chan Ho Park; Sung-Hwan Kim; In-Hyeon Kim; Won Gil Cho (Toxicology, 2024)

Three undescribed dimeric ferulates from the culture broth of Phellinus linteus and their dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Won-Gi Seo; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Production and separation of 2,5-furandicarboxylic acid in gamma-valerolactone solvent system using glucaric acid as raw material derived from oxidation of enzymatic hydrolysate of Miscanthus sacchariflorus - Jonghwa Kim; Jong-Chan Kim; Young-Min Cho; Chae-Hwi Yoon; Hyo Won Kwak; June-Ho Choi; Hoyong Kim; In-Gyu Choi (Biomass and Bioenergy, 2024)

Considering the Chemical Components of Particulate Matter 2.5 for Assessing Its Health Risks to Residents near the Ansan/Siheung and Ulsan Industrial Complexes - Ji-Yun Jung; Shin-Young Park; Jeong-In Jeon; Hye-Won Lee; Sung-Won Yoon; Cheol-Min Lee (Water, Air, & Soil Pollution, 2024)

Particulate matter-mediated oxidative stress induces airway inflammation and pulmonary dysfunction through TXNIP/NF-κB and modulation of the SIRT1-mediated p53 and TGF-β/Smad3 pathways in mice - Ji-Hye Ha; Ba-Wool Lee; Da-Hye Yi; Se-Jin Lee; Woong-Il Kim; So-Won Pak; Hyeon-Young Kim; Sung-Hwan Kim; In-Sik Shin; Jong-Choon Kim; In-Chul Lee (Food and Chemical Toxicology, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Enhancing Viability of Human Embryonic Stem Cells during Cryopreservation via RGD-REP-Mediated Activation of FAK/AKT/FoxO3a Signaling Pathway - Jeong Hee Kim; Jeong In Choi; Young Hyun Che; Su Haeng Sung; Hojae Lee; Sun Lee; Jae-Hoon Park; Yun-Il Lee; Young-Sam Lee; Won Bae Jeon; Yong Jun Kim (Tissue Engineering and Regenerative Medicine, 2023)

In situ electrolyte replenishment with atmospheric pressure-chemical/electrochemical vapour deposition for molten carbonate fuel cells - Kab In Kim; Jae Kwan Bae; Emilio Audasso; Albert Won Cho; Young Bae Jun; Hyun Seo Park; Seong-Cheol Jang; Yong Soo Cho; Han Sung Kim; Sun-Hee Choi; Sung Pil Yoon (Chemical Engineering Journal, 2023)

Mechanisms of interactions in pattern-recognition of common glycostructures across pectin-derived heteropolysaccharides by Toll-like receptor 4 - Gyu Hwan Hyun; In Ho Cho; Yoon Young Yang; Da-Hye Jeong; Yun Pyo Kang; You-Sun Kim; Seul Ji Lee; Sung Won Kwon (Carbohydrate Polymers, 2023)

A Study on Grid-Cell-Type Maritime Traffic Distribution Analysis Based on AIS Data for Establishing a Coastal Maritime Transportation Network - Hyun-Suk Kim; Eunkyu Lee; Eui-Jong Lee; Jin-Won Hyun; In-Young Gong; Kyungsup Kim; Yun-Sok Lee (Journal of Marine Science and Engineering, 2023)
Recently, marine development plans such as offshore wind farms and marina port facilities have been established to use Korean coastal waters, and research on the development of operational ships such as autonomous ships and water-surface flying ships is being rapidly promoted. Since the marine traffic in Korean coastal waters is expected to increase, the government intends to construct a coastal maritime transportation network that connects Korean coastal waters to guarantee safe ship navigation. Therefore, this study used automatic-identification-system data analysis to obtain quantitative evaluation results on maritime traffic distribution characteristics and utilization levels for the entire Korean coastal waters in grid cell for greater consistency and compatibility. The characteristics of marine traffic distribution at a certain site in coastal Korean waters can be quantitatively examined using the findings of this study, and they may be used as grid-cell-type data-based information. Moreover, the vessel traffic index allows for extensive research while quickly understanding the present level of use of the passing ships by the sea area. In this regard, the findings of this study are expected to be useful for the future development of maritime transportation networks in Korean coastal waters.

The insecticidal potential of Bacillus velezensis CE 100 against Dasineura jujubifolia Jiao & Bu (Diptera: Cecidomyiidae) larvae infestation and its role in the enhancement of yield and fruit quality of jujube (Zizyphus jujuba Miller var. inermis Rehder) - Su-In Choi; Henry B. Ajuna; Sang-Jae Won; Vantha Choub; Chul-Woo Kim; Jae-Hyun Moon; Young Sang Ahn (Crop Protection, 2023)

Normobaric hyperoxia re-sensitizes paclitaxel-resistant lung cancer cells - Jeonghyeon Im; Hee Young Kwon; In Kyoung Kim; Chang Dong Yeo; Sei Won Kim; Heayon Lee; Hye Seon Kang; Sang Haak Lee (Molecular & Cellular Toxicology, 2022)

Neuroprotective Effects of Purpurin Against Ischemic Damage via MAPKs, Bax, and Oxidative Stress Cascades in the Gerbil Hippocampus - Woosuk Kim; Hyun Jung Kwon; Hyo Young Jung; Kyu Ri Hahn; Yeo Sung Yoon; In Koo Hwang; Soo Young Choi; Dae Won Kim (Molecular Neurobiology, 2022)
Purpurin has various effects, including anti-inflammatory effects, and can efficiently cross the blood–brain barrier. In the present study, we investigated the effects of purpurin on oxidative stress in HT22 cells and mild brain damage in the gerbil hippocampal CA1 region induced by transient forebrain ischemia. Oxidative stress induced by H 2 O 2 was significantly ameliorated by treatment with purpurin, based on changes in cell death, DNA fragmentation, formation of reactive oxygen species, and pro-apoptotic (Bax)/anti-apoptotic (Bcl-2) protein levels. In addition, treatment with purpurin significantly reduced the phosphorylation of c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase 1/2 (ERK), and p38 signaling in HT22 cells. Transient forebrain ischemia in gerbils led to a significant increase in locomotor activity 1 day after ischemia and significant decrease in number of surviving cells in the CA1 region 4 days after ischemia. Administration of purpurin reduced the travel distance 1 day after ischemia and abrogates the neuronal death in the hippocampal CA1 region 4 days after ischemia based on immunohistochemical and histochemical staining for NeuN and Fluoro-Jade C, respectively. Purpurin treatment significantly decreased the activation of microglia and astrocytes as well as the increases of nuclear factor kappa-light-chain-enhancer of activated B cells p65 in the hippocampal CA1 region 4 days after ischemia and ameliorated the ischemia-induced transient increases of interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α in the hippocampus 6 h after ischemia. In addition, purpurin significantly alleviated the ischemia-induced phosphorylation of JNK, ERK, and p38 in the hippocampus 1 day after ischemia. Furthermore, purpurin treatment significantly mitigated the increases of Bax in the hippocampus 1 day after ischemia and the lipid peroxidation based on malondialdehyde and hydroperoxides levels 2 days after ischemia. These results suggest that purpurin can be one of the potential candidates to reduce neuronal damage and inflammatory responses after oxidative stress in HT22 cells or ischemic damage in gerbils.

Construction of full-length infectious cDNA clones of two Korean isolates of turnip mosaic virus breaking resistance in Brassica napus - Zheng-Xing Song; Eun-Young Seo; Wen-Xing Hu; Jong-Hyeon Jeong; Jae Sun Moon; Kang-Hee Kim; Won-Seob Eom; In-Sook Cho; John Hammond; Hyoun-Sub Lim (Archives of Virology, 2022)

Assessment of the abuse potential of methamnetamine in rodents: a behavioral pharmacology study - Dong-Hyun Youn; Jin Mook Kim; Young-ki Hong; Seo-In Park; Jin-Moo Lee; Young-Hoon Kim; Chang Won Park; Mi Sun Kang (Psychopharmacology, 2021)

Poor outcomes of early recurrent post-transplant bloodstream infection in living-donor liver transplant recipients - Si-Ho Kim; Seok Jun Mun; Jae-Hoon Ko; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Gyu-Seong Choi; Jong Man Kim; Jae-Won Joh; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Monitoring a short-lived earthquake swarm during April–May 2020 in Haenam, Korea, and its preliminary results - Jongwon Han; Wooseok Seo; Han-Joon Kim; Won-Young Kim; Deokhee Won; Ji-In Chung; Kwang-Hee Kim (Geosciences Journal, 2021)

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Identification of the prion-related protein gene (PRNT) sequences in various species of the Cervidae family - In-Soon Roh; Yong-Chan Kim; Hyo-Jin Kim; Sae-Young Won; Min-Ju Jeong; Hae-Eun Kang; Hyun-Joo Sohn; Byung-Hoon Jeong (Molecular Biology Reports, 2020)

Particle number size distributions generated by different Korean pork cooking methods - Soo Ran Won; In-Keun Shim; Myunghee Kwon; Hyun Ah Ji; Ki-soo Park; Young Sung Ghim (Air Quality, Atmosphere & Health, 2020)

Effects of the DNA repair inhibitors, cytosine arabinoside and 3-aminobenzamide, on the frequency of radiation-induced micronuclei, nuclear buds, and nucleoplasmic bridges - Yoon Hee Cho; Yang Jee Kim; Sunyeong Lee; Kyung-in Joung; Hai Won Chung; Sunmi Kim; Su Young Kim (Genes & Genomics, 2020)

Ischemia-related changes of fat-mass and obesity-associated protein expression in the gerbil hippocampus - Woosuk Kim; Min Soo Kang; Tae Hyeong Kim; Dae Young Yoo; Joon Ha Park; Hyo Young Jung; Moo-Ho Won; Jung Hoon Choi; In Koo Hwang (Metabolic Brain Disease, 2020)

Anti-skin ageing effects of phenolic compounds from Carpinus tschonoskii - Jun Yin; Hye Shin Ahn; Seong Yi Ha; In Hyeok Hwang; Kee Dong Yoon; Young Won Chin; Min Won Lee (Natural Product Research, 2019)

Tsunami hazard from submarine landslides: scenario-based assessment in the Ulleung Basin, East Sea (Japan Sea) - Roger Urgeles; Jang-Jun Bahk; Sang-Hoon Lee; Senay Horozal; Deniz Cukur; Seong-Pil Kim; Gil-Young Kim; Sueng-Won Jeong; In-Kwon Um (Geosciences Journal, 2019)

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Effects of degree and symmetricity of bilateral spectral smearing, carrier frequency, and subject sex on amplitude of evoked auditory steady-state response signal - Jong Ho Hwang; Kyoung Won Nam; Dong Pyo Jang; In Young Kim (Cognitive Neurodynamics, 2019)

Differential regional infarction, neuronal loss and gliosis in the gerbil cerebral hemisphere following 30 min of unilateral common carotid artery occlusion - Ji Hyeon Ahn; Minah Song; Hyunjung Kim; Tae-Kyeong Lee; Cheol Woo Park; Young Eun Park; Jae-Chul Lee; Jun Hwi Cho; Young-Myeong Kim; In Koo Hwang; Moo-Ho Won; Joon Ha Park (Metabolic Brain Disease, 2019)

Detection of Pathogenic Viruses in the Ambient Air in Seoul, Korea - Tae-Hee Han; Sang-Hun Park; Ju-Young Chung; Hyo-Won Jeong; Jihun Jung; Jae-In Lee; Young-Ok Hwang; Il-Young Kim; Jip-Ho Lee; Kweon Jung (Food and Environmental Virology, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

A discontinuity in the late Pleistocene alluvial deposits, Hwacheon‐ri, Gyeongju, Korea: Occurrences and paleoenvironmental implication - Hoil Lee; In Sung Paik; Hyun Joo Kim; Hee‐Cheol Kang; Won Gyeong Seol; Jin‐Young Lee (Island Arc, 2018)
A sedimentary discontinuity is present in the late Pleistocene alluvial deposits exposed along the cliff in stream side, Gyeongju, Korea. Sedimentological study, Optically Stimulated Luminescence (OSL) age dating, and X‐ray diffraction (XRD), and X‐ray fluorescence spectrometer (XRF) analyses were conducted in order to interpret the origin of the discontinuity surface. Based on the sedimentological study, these deposits can be divided into three distinct stages, in ascending order: (Stage 1) development of a braided stream flowing from south to north and deposition by debris flows from the mountain aside the stream during and/or after deposition of the braided stream; (Stage 2) deposition by intermittent events during a state of stagnation after the abandonment or migration of the previously existed braided stream; and (Stage 3) deposition of gravels from debris flows from the mountain aside the stream. Hornfelsic gravels are common in Stage 1, whereas andesitic gravels are predominant in Stage 3, suggesting the provenance change from Stage 1 to Stage 3. The discontinuity surface is laterally extensive and marked by a distinct carbonaceous dark grey horizon between Stage 2 and Stage 3. It is characteristic that rootlets mineralized by vivianite are present, and iron‐oxide crusts are cutting across irregularly below the discontinuity surface. It is thus interpreted that the shift of depositional environment from an alluvial plain (Stage 2) (125 ka) to an alluvial fan (Stage 3) (94–55 ka) was an alluvial response to sea level change from the interglacial to the glacial. The development of iron‐oxide crusts and diagenetic vivianite in the discontinuity surface suggests humid condition persisted during the paleoclimatic shift from the last interglacial to the last glacial stages.

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Decreased Metabolism in the Posterior Medial Network with Concomitantly Increased Metabolism in the Anterior Temporal Network During Transient Global Amnesia - SangHak Yi; Young Ho Park; Jae-Won Jang; Jae-Sung Lim; In Kook Chun; SangYun Kim (Brain Topography, 2018)

Dendropanax morbifera Léveille extract ameliorates cesium-induced inflammation in the kidney and decreases antioxidant enzyme levels in the hippocampus - Hyo Young Jung; Hyun Jung Kwon; Kyu Ri Hahn; Dae Young Yoo; Woosuk Kim; Jong Whi Kim; Yong Jae Kim; Yeo Sung Yoon; Dae Won Kim; In Koo Hwang (Molecular & Cellular Toxicology, 2018)

Effects of spectral smearing of stimuli on the performance of auditory steady-state response-based brain–computer interface - Jong Ho Hwang; Kyoung Won Nam; Dong Pyo Jang; In Young Kim (Cognitive Neurodynamics, 2017)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

Ssanghwa-Tang, a traditional herbal formula, suppresses cigarette smoke-induced airway inflammation via inhibition of MMP-9 and Erk signaling - Je-Won Ko; Na-Rae Shin; Sung-Hyeuk Park; In-Chul Lee; Jung-Min Ryu; Young-Kwon Cho; Jong-Choon Kim; Chang-Seob Seo; In-Sik Shin (Molecular & Cellular Toxicology, 2017)

Genetic characteristics of highly pathogenic H5N8 avian influenza viruses isolated from migratory wild birds in South Korea during 2014-2015 - Young-Jae Si; Won Suk Choi; Young-Il Kim; In-Won Lee; Hyeok-Il Kwon; Su-Jin Park; Eun-Ha Kim; Se mi Kim; Jin-Jung Kwon; Min-Suk Song; Chul-Joong Kim; Young-Ki Choi (Archives of Virology, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

Directing human embryonic stem cells towards functional endothelial cells easily and without purification - Chang-Hyun Gil; Byeong-Seong Ki; Joseph Seo; Jong-Jin Choi; Hana Kim; In-Gul Kim; A.-Ra Jung; Won-Young Lee; Youngsok Choi; Kwideok Park; Sung-Hwan Moon; Hyung-Min Chung (Tissue Engineering and Regenerative Medicine, 2016)

First record of massive blooming of benthic diatoms and their association with megabenthic filter feeders on the shallow seafloor of an Antarctic Fjord: Does glacier melting fuel the bloom? - In-Young Ahn; Hye-Won Moon; Misa Jeon; Sung-Ho Kang (Ocean Science Journal, 2016)

PARK2 gene variants in Korean patients with Parkinson’s disease - Min-young Park; In won Park; Chun hwa Ihm; Eunhee Kim (Genes & Genomics, 2016)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

The role of APCDD1 in epithelial rearrangement in tooth morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Gi-Jeong Gwon; Ki-Rim Kim; Sanggyu Lee; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Hitoshi Yamamoto; Sung-Won Cho; Youngkyun Lee; Jae-Young Kim (Histochemistry and Cell Biology, 2015)

Abundance and Distribution Characteristics of Microplastics in Surface Seawaters of the Incheon/Kyeonggi Coastal Region - Doo-Hyeon Chae; In-Sung Kim; Seung-Kyu Kim; Young Kyoung Song; Won Joon Shim (Archives of Environmental Contamination and Toxicology, 2015)

Erratum to: Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2015)

Arabidopsis Qc-SNARE gene AtSFT12 is involved in salt and osmotic stress responses and Na+ accumulation in vacuoles - Vaishali N. Tarte; Hye-Yeon Seok; Dong-Hyuk Woo; Dinh Huan Le; Huong T. Tran; Ji-Won Baik; In Soon Kang; Sun-Young Lee; Taijoon Chung; Yong-Hwan Moon (Plant Cell Reports, 2015)

Effects of phenotypic and RAPD variations on ecophysiological characterization of reeds (Phragmites australis) in Suncheon Bay - In Seon Jeon; Da Som Kwon; Hoon Shin; Won Bok Kim; Na Roo Kang; Sun Mi Whang; Mi Sun Kim; Soo Jin Wi; Ky Young Park (Journal of Plant Biology, 2015)

Analysis of cytokine production in a newly developed canine tracheal epithelial cell line infected with H3N2 canine influenza virus - Woo-Jung Park; Byung-Joo Park; Young-Jo Song; Dong-Hun Lee; Seong-Su Yuk; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Archives of Virology, 2015)

Developmental regulations of Perp in mice molar morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Girdhari Rijal; Ye-Ji Lee; Sanggyu Lee; Hitoshi Yamamoto; Chang-Hyeon An; Sung-Won Cho; Youngkyun Lee; Hong-In Shin; Tae-Yub Kwon; Jae-Young Kim (Cell and Tissue Research, 2014)

Antimicrobial peptides in the centipede Scolopendra subspinipes mutilans - Won Gi Yoo; Joon Ha Lee; Younhee Shin; Jae-Young Shim; Myunghee Jung; Byeong-Chul Kang; Jaedon Oh; Jiyeon Seong; Hak Kyo Lee; Hong Sik Kong; Ki-Duk Song; Eun-Young Yun; et al. (Functional & Integrative Genomics, 2014)

Halapricum salinum gen. nov., sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - Hye Seon Song; In-Tae Cha; Kyung June Yim; Hae-Won Lee; Dong-Wook Hyun; Sung-Jae Lee; Sung-Keun Rhee; Kil-Nam Kim; Daekyung Kim; Jong-Soon Choi; Myung-Ji Seo; Hak-Jong Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halolamina rubra sp. nov., a haloarchaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Jong-Soon Choi; Daekyung Kim; Sung-Jae Lee; Myung-Ji Seo; Hak-Jong Choi; Jin-Woo Bae; et al. (Antonie van Leeuwenhoek, 2014)

Halobellus rufus sp. nov., an extremely halophilic archaeon isolated from non-purified solar salt - In-Tae Cha; Kyung June Yim; Hye Seon Song; Hae-Won Lee; Dong-Wook Hyun; Kil-Nam Kim; Myung-Ji Seo; Daekyung Kim; Jong-Soon Choi; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; et al. (Antonie van Leeuwenhoek, 2014)

Halorubrum halophilum sp. nov., an extremely halophilic archaeon isolated from a salt-fermented seafood - Kyung June Yim; In-Tae Cha; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Sung-Jae Lee; Young-Do Nam; Dong-Wook Hyun; Jin-Woo Bae; Sung-Keun Rhee; Myung-Ji Seo; Jong-Soon Choi; et al. (Antonie van Leeuwenhoek, 2014)

Halococcus sediminicola sp. nov., an extremely halophilic archaeon isolated from a marine sediment - Kyung June Yim; In-Tae Cha; Tae Woong Whon; Hae-Won Lee; Hye Seon Song; Kil-Nam Kim; Young-Do Nam; Sung-Jae Lee; Jin-Woo Bae; Sung-Keun Rhee; Jong-Soon Choi; Myung-Ji Seo; et al. (Antonie van Leeuwenhoek, 2014)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

Characterization of functional variants in 33 blood pressure loci using 1000 genomes project data - Ji Eun Lim; Young-Ah Shin; Kyung-Won Hong; Hyun-Seok Jin; In Song Koh; Bermseok Oh (Genes & Genomics, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

The green algae Ulva fasciata Delile extract induces apoptotic cell death in human colon cancer cells - Min Ju Ryu; Areum Daseul Kim; Kyoung Ah Kang; Ha Sook Chung; Hye Sun Kim; In Soo Suh; Weon Young Chang; Jin Won Hyun (In Vitro Cellular & Developmental Biology - Animal, 2013)

Volumetric Analysis of Cerebellum in Short-Track Speed Skating Players - In Sung Park; Nam Joon Lee; Tae-Young Kim; Jin-Hoon Park; Yu-Mi Won; Yong-Ju Jung; Jin-Hwan Yoon; Im Joo Rhyu (The Cerebellum, 2012)

Chondracanthus tenellus (Harvey) hommersand extract protects the human keratinocyte cell line by blocking free radicals and UVB radiation-induced cell damage - Mei Jing Piao; Yu Jae Hyun; Tae-Heon Oh; Hee Kyoung Kang; Eun Sook Yoo; Young Sang Koh; Nam Ho Lee; In Soo Suh; Jin Won Hyun (In Vitro Cellular & Developmental Biology - Animal, 2012)

Evaluation of soybean cultivars for resistance to phomopsis seed decay in Korea - Suli Sun; Kyujung Van; Moon Young Kim; Yeong-Ho Lee; Jong-Min Ko; In-Youl Baek; Yin-Won Lee; Weixian Liu; Suk-Ha Lee (Journal of Crop Science and Biotechnology, 2012)

Determination of endocrine disrupting chemicals in water samples by dispersive liquid–liquid microextraction combined with liquid chromatography–fluorescence detection - Yeonsuk Ryu; Jung-In Lee; Jae-Won Moon; Jung-Hyun Kim; Ji-Hwan Park; Su-Yeon Park; Young A. Yoon; Jeongmi Lee (Journal of Pharmaceutical Investigation, 2012)

Salt effect of nisin Z isolated from a marine fish on the growth inhibition of Streptococcus iniae, a pathogen of streptococcosis - Won-Seok Heo; Eun-Young Kim; Yu-Ri Kim; Muhammad Tofazzal Hossain; In-Soo Kong (Biotechnology Letters, 2012)

Comparative analysis of expressed sequence tags (ESTs) between normal group and softness syndrome group in Halocynthia roretzi - Ji Eun Jeong; Se Won Kang; Yun Kyung Shin; Je Cheon Jun; Young-Ok Kim; Young Baek Hur; Jae-Hyung Kim; Sung-Hwa Chae; Jun-Sang Lee; In ho Choi; Yeon Soo Han; Dae-Hyun Seog; et al. (Molecular & Cellular Toxicology, 2011)

Developmental expression of plasma glutathione peroxidase during mouse organogenesis - Ki Youn Jung; In-Jeoung Baek; Jung-Min Yon; Se-Ra Lee; Mi-Ra Kim; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2011)

Temperature trends in the skin/surface, mid-troposphere and low stratosphere near Korea from satellite and ground measurements - Jung-Moon Yoo; Young-In Won; Young-Jun Cho; Myeong-Jae Jeong; Dong-Bin Shin; Suk-Jo Lee; Yu-Ri Lee; Soo-Min Oh; Soo-Jin Ban (Asia-Pacific Journal of Atmospheric Sciences, 2011)

Phospholipid hydroperoxide glutathione peroxidase gene is regulated via an estrogen and estrogen receptor signaling in cultured mouse fetuses - In-Jeoung Baek; Ki Youn Jung; Jung-Min Yon; Se-Ra Lee; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (In Vitro Cellular & Developmental Biology - Animal, 2011)

A new cloning strategy for generating multiple repeats of a repetitive polypeptide based on non-template PCR - Hun-Su Chu; Jung Ryum; Seo-Young Park; Byung-Gee Kim; Dong-Myung Kim; Jong-In Won (Biotechnology Letters, 2011)

Molecular characterization of rotavirus diarrhea among children in South Korea: detection of an unusual G11 strain - Jung Ok Shim; In Hyuk Baek; Van Phan Le; Eun-Mi Ko; Won-Seok Seok; Young Uh; Ja Kyoung Kim; Sung Yeon Ahn; Hyeon Soo Lee; Eell Ryoo; So-Yeon Shim; Wonkeun Song; et al. (Archives of Virology, 2011)

A possible association of EMID2 polymorphisms with aspirin hypersensitivity in asthma - Charisse Flerida A. Pasaje; Jeong-Hyun Kim; Byung-Lae Park; Hyun Sub Cheong; Mi-Kyeong Kim; Inseon S. Choi; Sang Heon Cho; Chein-Soo Hong; Yong Won Lee; Jae-Young Lee; In Song Koh; Tae-Joon Park; et al. (Immunogenetics, 2011)

Determining hypocentral parameters for local earthquakes under ill conditions using genetic algorithm - Woohan Kim; In-Kyeong Hahm; Won-Young Kim; Jung Mo Lee (Journal of Seismology, 2010)

AtObgC, a plant ortholog of bacterial Obg, is a chloroplast-targeting GTPase essential for early embryogenesis - Woo Young Bang; Akira Hata; In Sil Jeong; Tetsuya Umeda; Takayuki Masuda; Ji Chen; Ishizaki Yoko; I Nengah Suwastika; Dae Won Kim; Chak Han Im; Byung Hyun Lee; Yuno Lee; et al. (Plant Molecular Biology, 2009)

Population-specific QTLs and their different epistatic interactions for pod dehiscence in soybean [Glycine max (L.) Merr.] - Sung-Taeg Kang; Myounghai Kwak; Hyeun-Kyeung Kim; Myoung-Gun Choung; Won-Young Han; In-Youl Baek; Moon Young Kim; Kyujung Van; Suk-Ha Lee (Euphytica, 2009)

Antimicrobial effect and resistant regulation of Glycyrrhiza uralensis on methicillin-resistant Staphylococcus aureus - Ji-Won Lee; Young-Ju Ji; Mi-Hee Yu; Mi-Hyang Hwang Bo; Hwa-Jeong Seo; Sam-Pin Lee; In-Seon Lee (Natural Product Research, 2009)

The spatio-temporal expression pattern of cytoplasmic Cu/Zn superoxide dismutase (SOD1) mRNA during mouse embryogenesis - Jung-Min Yon; In-Jeoung Baek; Se-Ra Lee; Yan Jin; Mi-Ra Kim; Sang-Seop Nahm; Jong-Soo Kim; Byeongwoo Ahn; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2008)

15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) sensitizes human leukemic HL-60 cells to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis through Akt downregulation - Hoon Han; Sung-Won Shin; Chi-Yeon Seo; Hyuk-Chan Kwon; Jin-Yeong Han; In-Hoo Kim; Jong-Young Kwak; Joo-In Park (Apoptosis, 2007)

Biomass accumulations and the distribution of nitrogen and phosphorus within threeQuercus acutissima stands in central Korea - Nam Jin Noh; Yowhan Son; Rae Hyun Kim; Kyung Won Seo; Jin Woo Koo; In Hyeop Park; Young Jin Lee; Kyeong Hak Lee; Yeong Mo Son (Journal of Plant Biology, 2007)

Tissue expression and cellular localization of phospholipid hydroperoxide glutathione peroxidase (PHGPx) mRNA in male mice - In-Jeoung Baek; Dong-Suk Seo; Jung-Min Yon; Se-Ra Lee; Yan Jin; Sang Soep Nahm; Jae-Hwang Jeong; Young-Kug Choo; Jong-Koo Kang; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2007)

Enhanced brain targeting efficiency of intranasally administered plasmid DNA: an alternative route for brain gene therapy - In-Kwon Han; Mi Young Kim; Hyang-Min Byun; Tae Sun Hwang; Jung Mogg Kim; Kwang Woo Hwang; Tae Gwan Park; Woon-Won Jung; Taehoon Chun; Gil-Jae Jeong; Yu-Kyoung Oh (Journal of Molecular Medicine, 2006)

Monitoring the occurrence of genetically modified soybean and maize around cultivated fields and at a grain receiving port in Korea - Chang-Gi Kim; Hoonbok Yi; Sangkyu Park; Ji Eun Yeon; Do Young Kim; Dae In Kim; Kyu-Hwa Lee; Taek Chang Lee; In Soon Paek; Won Kee Yoon; Soon-Chun Jeong; Hwan Mook Kim (Journal of Plant Biology, 2006)

p53 and cell-cycle-regulated protein expression in small intestinal cells after fast-neutron irradiation in mice - Young-Heun Jee; Won-Il Jeong; Tae-Hwan Kim; In-Sun Hwang; Mee-Jung Ahn; Hong-Gu Joo; Su-Hyung Hong; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2005)

Production of biologically active human granulocyte colony stimulating factor in the milk of transgenic goat - Jung Ho Ko; Chul-Sang Lee; Kui Hyun Kim; Myung-Geol Pang; Ja Shin Koo; Nanzhu Fang; Deog-Bon Koo; Keon Bong Oh; Woo-Sik Youn; Guo Dong Zheng; Jung Sun Park; Sun Jung Kim; et al. (Transgenic Research, 2000)

Stimulation of β-carotene synthesis by hydrogen peroxide in Blakeslea trispora - Jae-Cheol Jeong; In-Young Lee; Seon-Won Kim; Young-Hoon Park (Biotechnology Letters, 1999)

A ncovel angiogenic factor derived from Aloe vera gel: β-sitosterol, a plant sterol - Eun-Joung Moon; You Mie Lee; Ok-Hee Lee; Myoung-Jin Lee; Seung-Ki Lee; Myung-Hee Chung; Young-In Park; Chung-Ki Sung; Jae-Soo Choi; Kyu-Won Kim (Angiogenesis, 1999)